Estimation earthquake occurrence probability in Kamchatka region based on seismological and complex of ionospheric precursors - Boganov Vadim (EDP Sciences, 2021)
In this paper the authors present the method of estimation of a region, waiting period and probability of strong earthquakes with KS ≥ 13.5 (M ≥ 6.0) in Kamchatka region based on the combination of mid-term and short-term predictive signs accompanying earthquake formation. The seismological predictive parameter ξP was taken as a mid-term precursor. It was calculated on the basis of the probabilistic model of seismic regime. A complex of ionospheric parameters was considered as short-term predictive signs with an earthquake waiting period of up to 5 days. It includes the K-layer, the sporadic Es layer of the r type, the critical frequency foF2, and the frequency stratification of the F2 layer. The probabilities of strong earthquakes with KS ≥ 13.5 (M ≥ 6.0) that occurred over the period 2019–2021 in an expected zone, determined by the parameter ξP, were estimated on the basis of Bayes method provided that a complex of anomalous parameters of the ionosphere was identified.